Does spinal cord stimulation improve gait in Parkinson's disease: A comprehensive review. (April 2023) - Streumer, Jesco; Selvaraj, Ashok K.; Kurt, Erkan; Bloem, Bastiaan R.; Esselink, Rianne A.J.; Bartels, Ronald H.M.A.; Georgiev, Dejan; Vinke, R. Saman
Abstract: Introduction: Axial disability, including gait disturbances, is common in Parkinson's disease (PD), especially in advanced stages. Epidural spinal cord stimulation (SCS) has been investigated as a treatment option for gait disorders in PD. Here, we review the literature on SCS in PD and evaluate its efficacy, optimal stimulation parameters, optimal electrode locations, possible effects of concurrent deep brain stimulation, and possible working mechanisms on gait. Methods: Databases were searched for human studies involving PD patients who received an epidural SCS intervention and who had at least one gait-related outcome measure. The included reports were reviewed with respect to design and outcomes. Additionally, the possible mechanisms of action underlying SCS were reviewed. Results: Out of 433 records identified, 25 unique studies with in total 103 participants were included. Most studies included only a few participants. The gait disorders of most PD patients with concurrent pain complaints, mostly low back pain, improved with SCS in almost all cases, regardless of stimulation parameters or electrode location. Higher-frequency stimulation (>200 Hz) seemed to be more effective in pain-free PD patients, but the results were inconsistent. Heterogeneity in outcome measures and follow-up times hindered comparability. Conclusions: SCS may improve gait in PD patients with neuropathic pain, but its efficacy in pain-free patients remains uncertain due to a lack of thorough double-blind studies. Apart from a well-powered, controlled, double-blind study design, future studies could further explore the initial hints that higher-frequency stimulation (>200 Hz) might be the best approach to improve gait outcomes in pain-free patients. Highlights: We review the effect of spinal cord stimulation on gait in PD. 25 studies with in total 103 participants were included. The gait of most PD patients with concurrent pain complaints improved with spinal cord stimulation. Higher-frequency stimulation seemed to be more effective in pain-free PD patients. Well-controlled, double-blind studies are needed to explore the effect of spinal cord stimulation on gait in PD.